2004
DOI: 10.1021/es048648p
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Concentrations and Air−Water Flux of Organochlorine Pesticides along the Western Antarctic Peninsula

Abstract: Air, seawater, sea ice, and snow were collected during the austral winter (September-October 2001) and summer (January-February 2002) along the Western Antarctic Peninsula. Hexachlorobenzene (HCB) > heptachlor > alpha- and gamma-hexachlorocyclohexane (HCH) and heptachlor epoxide, were the most frequently detected organochlorine pesticides in air. HCB and HCH levels declined over the past 20 years, with a half-life of 3 years for sigmaHCH in Antarctic air. However, heptachlor epoxide levels have not declined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 26 publications
13
64
0
Order By: Relevance
“…1a) ranged from 12 to 37 pg m −3 (mean: 27 ± 11 pg m −3 ) in the Northern Hemisphere (NH), and from 1.5 to 4.0 pg m −3 (mean: 2.8 ± 1.1 pg m −3 ) in the Southern Hemisphere (SH). Our results were comparable to those of global oceans (Wong et al, 2011;Wu et al, 2010;Lakaschus et al, 2002;Dickhut et al, 2005;Ding et al, 2007). The highest concentration was present in the coast near Western Europe and northwestern Africa (37 pg m −3 ) and the lowest concentration was observed in Southern Ocean (1.5 pg m −3 ).…”
Section: Hchs In the Atmospheresupporting
confidence: 88%
See 2 more Smart Citations
“…1a) ranged from 12 to 37 pg m −3 (mean: 27 ± 11 pg m −3 ) in the Northern Hemisphere (NH), and from 1.5 to 4.0 pg m −3 (mean: 2.8 ± 1.1 pg m −3 ) in the Southern Hemisphere (SH). Our results were comparable to those of global oceans (Wong et al, 2011;Wu et al, 2010;Lakaschus et al, 2002;Dickhut et al, 2005;Ding et al, 2007). The highest concentration was present in the coast near Western Europe and northwestern Africa (37 pg m −3 ) and the lowest concentration was observed in Southern Ocean (1.5 pg m −3 ).…”
Section: Hchs In the Atmospheresupporting
confidence: 88%
“…From the Equator to Cape Town, [α-HCH] gas were similar to those measured in 1999, whereas [γ -HCH] gas decreased by factor of 10, which likely results from the global reduction of lindane usage in the late 1990s (Lakaschus et al, 2002). From Cape Town (32 • S) to Neumayer Station (70.4 • S) (A14-A17) concentrations of α-, γ -and β-HCH were relatively constant and comparable to those measured in 1999 (Lakaschus et al, 2002), and along the Western Antarctic peninsula (Dickhut et al, 2005), illustrating background levels of HCHs in the Southern Ocean.…”
Section: Hchs In the Atmospheresupporting
confidence: 65%
See 1 more Smart Citation
“…Compared with other studies, the concentration of HCHs in this study was lower than that previously reported in studies on bulk seawater close to land conducted elsewhere in Southeast Asia (ranges from 430 to 42200 pg/L) (UNEP, 2002;Wurl and Obbard, 2005), and slightly higher than that previously reported in studies performed on Bering Sea and Chukchi Sea (144 to 683 pg/L for α-HCH, 30 to 196 pg/L for γ-HCH) (Yao et al, 2002), the Arctic Ocean (γ-HCH ranged from b 0.70 to 894 pg/L) (Weber et al, 2006). In addition, HCH concentration was much higher than that previously reported in studies conducted in the open seas, such as the Indian Ocean or the Atlantic Ocean and open sea along the Western Antarctic Peninsula (Dickhut et al, 2005;Jaward et al, 2004). Similar to HCHs, the levels of DDTs in this study were at the upper limits of the reported figure worldwide (Yao et al, 2002).…”
Section: Concentrations In Watermentioning
confidence: 87%
“…For example, invasive alien species have profoundly altered species assemblages and ecosystem functioning on most sub-Antarctic islands, and their direct effects are starting to be felt on the continent itself (Frenot et al 2005), often in ways that are not immediately obvious (Kerry 1990;Wynn-Williams 1996;Hughes 2003). Indirect human influences include the long-range transport to and the presence of persistent organic and inorganic pollutants in Antarctic systems (Corsolini et al 2002;Bargagli 2005;Dickhut et al 2005), and the substantial alterations to terrestrial communities as a consequence of changing climates associated with global warming Bergstrom & Chown 1999;Walther et al 2002;Convey 2003a). The significance of these impacts, and their scope for increase, given ongoing global change ( Watson 2002) and growing human use of the Antarctic ( Naveen et al 2001;Frenot et al 2005), have been recognized by the Committee for Environmental Protection of the Antarctic Treaty System, and by those nations that have responsibility for the sub-Antarctic islands (e.g.…”
Section: Introductionmentioning
confidence: 99%